2020
DOI: 10.1186/s12890-020-01354-w
|View full text |Cite
|
Sign up to set email alerts
|

Application of high-flow nasal cannula in hypoxemic patients with COVID-19: a retrospective cohort study

Abstract: Background It had been shown that High-flow nasal cannula (HFNC) is an effective initial support strategy for patients with acute respiratory failure. However, the efficacy of HFNC for patients with COVID-19 has not been established. This study was performed to assess the efficacy of HFNC for patients with COVID-19 and describe early predictors of HFNC treatment success in order to develop a prediction tool that accurately identifies the need for upgrade respiratory support therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
74
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 27 publications
14
74
0
5
Order By: Relevance
“…Several studies have reported the use of HFNC in COVID-19 patients (Geng et al, 2020;Wang et al, 2020;Chandel et al, 2020;Hu et al, 2020;Xu et al, 2020a). These studies showed that the rates of HFNC failure were between 38 and 45%, which agreed with the failure rate in our study (44%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have reported the use of HFNC in COVID-19 patients (Geng et al, 2020;Wang et al, 2020;Chandel et al, 2020;Hu et al, 2020;Xu et al, 2020a). These studies showed that the rates of HFNC failure were between 38 and 45%, which agreed with the failure rate in our study (44%).…”
Section: Discussionsupporting
confidence: 92%
“…As the variables required to calculate the ROX index are easy to obtain, even in the resourcelimited area, it may be helpful for the physicians to early identify patients with a high likelihood of success and those who will require escalation therapy. Apart from the ROX index, the advanced age, increased SOFA score, and decreased platelets were also reported to be associated with increased HFNC failure (Hu et al, 2020;Xu et al, 2020a). As such, the combined use of these variables and the ROX index might help improve the predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In this clinical setting, the efficacy of HFNC in inpatients with COVID-19 has previously been evaluated, in particular when hypoxic respiratory failure is present. The study proved that HFNC was an effective treatment for these patients, and approximately 61.9% of patients showed improved oxygenation and were also able to successfully withdraw from HFNC when treated at home [2] To date, there are no known studies describing at-home management of COVID-19 patients with respiratory failure with the use of HFNC.…”
Section: Introductionmentioning
confidence: 87%
“…No deaths were reported in the HFNC success group with a shorter median ICU stay (7 days [4][5][6][7][8] vs 23 days [18-42], P = .0015) and a greater percentage of hospital discharge at day 28, 16 (73%) vs 1 (0.5%; P = .00001) than the HFNC failure group.…”
mentioning
confidence: 96%